Metabolome and transcriptome integration reveals insights into the process of delayed petal abscission in rose by STS - Zhang, Jingjing; Zhang, Yuyun; He, Yongmei; Du, Tingting; Shan, Duoxiu; Fan, Houdong; Wang, Wenyu; Qin, Zhe; Xin, Cuihua; Pei, Haixia (Frontiers in Plant Science, 2022)
The abscission of plant organs plays an important role in ensuring the normal life activities. Rose, as one of the most important ornamental plants, its premature petal abscission has seriously affected the quality and commercial value. Silver Thiosulfate (STS) is an ethylene inhibitor, which is often used preservative to delay the senescence of fresh cut flowers. To understand the regulatory mechanism of petal abscission in rose by STS, integrative analysis of the metabolome and transcriptome profiles was performed in AZ tissues of rose under different treatments (MOCK, STS, Eth, STS+Eth). The results showed that STS affected the levels of five metabolites (Shikonin, Jasmonic acid, Gluconolactone, Stachyose and D-Erythrose 4-phosphate), and involved changes in the expression of 39 differential genes. Five DEGs (LOC112192149, LOC112196726, LOC112189737, LOC112188495, and LOC112188936) were directly associated with the biosynthesis of Shikonin, Jasmonic acid, and D-Erythrose 4-phosphate. Meanwhile, we found that STS had a greater effect on 14 transcription factor family during abscission. The effect on hormones was mainly focused on auxin and ethylene-related DEGs, and that STS delayed the abscission of rose petals might be related to plant innate immunity and disease resistance. Our results provided a new idea for understanding the mechanism of STS delaying petal abscission of rose.